2018
DOI: 10.3390/genes9080391
|View full text |Cite
|
Sign up to set email alerts
|

PRDM Histone Methyltransferase mRNA Levels Increase in Response to Curative Hormone Treatment for Cryptorchidism-Dependent Male Infertility

Abstract: There is a correlation between cryptorchidism and an increased risk of testicular cancer and infertility. During orchidopexy, testicular biopsies are performed to confirm the presence of type A dark (Ad) spermatogonia, which are a marker for low infertility risk (LIR). The Ad spermatogonia are absent in high infertility risk (HIR) patients, who are treated with a gonadotropin-releasing hormone agonist (GnRHa) to significantly lower the risk of infertility. Despite its prevalence, little is known about the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Furthermore, we found lower levels of PRDM1 , PRDM6 , PRDM9 , PRDM13 , and PRDM14 mRNA in the testes of patients with HIR compared to LIR, and PRDM7 , PRDM9 , PRDM12 , and PRDM16 were significantly induced after GnRHa treatment. Thus, GnRHa treatment induces an alternate pathway to stimulate PRDM9 for Ad spermatogonia specification without the permissive role of BMP4 , but increased the expression of BMP5 (log2FC = 2.31; FDR = 0.0001;) [12, 47]. LINC01121 is expressed upstream of SIX2 and may therefore influence its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found lower levels of PRDM1 , PRDM6 , PRDM9 , PRDM13 , and PRDM14 mRNA in the testes of patients with HIR compared to LIR, and PRDM7 , PRDM9 , PRDM12 , and PRDM16 were significantly induced after GnRHa treatment. Thus, GnRHa treatment induces an alternate pathway to stimulate PRDM9 for Ad spermatogonia specification without the permissive role of BMP4 , but increased the expression of BMP5 (log2FC = 2.31; FDR = 0.0001;) [12, 47]. LINC01121 is expressed upstream of SIX2 and may therefore influence its expression.…”
Section: Discussionmentioning
confidence: 99%
“…It acts in synergy with Prdm1 and TFAP2C (encoding AP2γ) to promote pluripotency and germline-specific gene expression, while repressing somatic genes (Magnúsdóttir et al, 2013; Nakaki et al, 2013; Sybirna et al, 2020; Yamaji et al, 2008). The absence of Prdm14 leads to a deficiency of PGCs and therefore, results in sterility (Hadziselimovic et al, 2018; Ohinata et al, 2009; Okuzaki et al, 2019; Sybirna et al, 2020; Yamaji et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…PRDM family proteins are characterized by the presence of highly conserved structural domains, the so-called positive regulatory/suppressor of variegation, enhancer of zeste, trithorax and C 2 H 2 -like zinc finger domains [ 13 ]. As transcriptional regulators, these molecules often control various aspects of cell differentiation and organism development, and when dysregulated, they are involved in carcinogenesis [ 14 17 ]. Recent reports have suggested that PRDM4 is implicated in cell signal transduction, cell proliferation, and differentiation [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%